(untitled) (Nexo Revista Científica, 2023)
Aim of the present study is to make satisfied the visitors (patients) through the offered services. There are private and public sector health care Centre’s in the Kingdom of Saudi Arabia, particularly in the diplomatic city of Riyadh. However, present study targeted public sector health care centers due to easy access. Later the study conceptualized a theoretical study framework and suggested the hypotheses based on the previous studies and recommendations. Thus, the study investigated the considered hypotheses for the mentioned variables. Total four (4) constructs were considered and four hypotheses were developed. Among 350 participants of the survey, valid responses were counted as 262. The collected data were analyzed through SPSS version 22. Descriptive part also included in the distributed questionnaire in order to obtained the respondents demographics. After analysis of the data, results showed all the hypotheses are having a significant relationship with each other. Findings of this study also important for the practitioners in health care sectors.